The foF2 depression over pameungpeuk during solar minimum and its application on HF radio communication - Jiyo Jiyo; Wahyu Pamungkas; Syifa Namira Ramadhani (JURNAL INFOTEL, 2022)
The foF2 depression of the ionosphere layer is a reference for determining the maximum usable frequency depression for an HF communication circuit. This paper discusses the foF2 depression observed at the Pameungpeuk observation station ((7.65°S, 107.96°E; inclination 32.38°S), in 2018 - 2021 when solar activity is minimum and the sun is at a minimum, but the foF2 depression continues to occur up to the severe level. Likewise, geomagnetic disturbances also occur to a moderate level, so that geomagnetic disturbances are a potential cause of foF2 depression. Another result is that the temporal variation pattern of the foF2 depression is less clear so that statistical models cannot be used. The correlation between the number of occurrences of foF2 depression in a month and the number of occurrences of geomagnetic disturbances is relatively low and found in months without the occurrence of geomagnetic disturbances but still foF2 depression occurs, so that geomagnetic disturbances are not the only cause of foF2 depression. Another possibility is the cause of foF2 depression is solar eclipse. In the application, information on the prediction of the foF2 depression that will occur can be used in frequency management, so that a frequency channel is obtained that matches the reflectivity of the ionospheric layer during operation. Anomalies of solar activity and geomagnetic disturbances can be used as inputs in predicting the foF2 depression.